2003
DOI: 10.1002/ange.200219816
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of a Hydrogen‐Bonded Charge‐Transfer State of 4‐Dimethylaminobenzonitrile in Methanol by Time‐Resolved IR Spectroscopy

Abstract: Charge-transfer excited states have frequently been studied by using 4-dimethylaminobenzonitrile (DMABN) as a model. In nonpolar solvents, a single fluorescence band is observed from a locally excited (LE) state. In polar solvents, the initially populated LE state reacts further to produce a stable intramolecular charge-transfer (ICT) state, which gives rise to a second fluorescence band that overlaps with, but is abnormally red-shifted from, the LE emission.[1] Results of experiments using aprotic solvents ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
175
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(208 citation statements)
references
References 26 publications
30
175
3
Order By: Relevance
“…The results are consistent with the structures being at the minima, and agree with the previous B3LYP results [14] and experiments [10,14,46,47] with respect to both the magnitude and assigned vibrational modes (see Table 2). …”
Section: Wwwchemphyschemorgsupporting
confidence: 93%
See 2 more Smart Citations
“…The results are consistent with the structures being at the minima, and agree with the previous B3LYP results [14] and experiments [10,14,46,47] with respect to both the magnitude and assigned vibrational modes (see Table 2). …”
Section: Wwwchemphyschemorgsupporting
confidence: 93%
“…The spin-free MS-CASPT2 vertical excitation energies (T v ) and oscillator strengths (f) of the five lowest-lying spin-free states of CH 2 BrI, iso-CH 2 Br-I, and iso-CH 2 I-Br. [8,9,47] have shown that photoexcitation of CH 2 BrI within the A-band absorption results in only CÀI bond cleavage.…”
Section: Assignment Of the A-bandmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,6,9,10,[56][57][58] The still faster ICT reaction found here for AZABN4F in n-hexane (7.7 10 12 s À1 or t 2 = 0.13 ps) as compared with DEABN4F, however, is contrary to the slowing down of the ICT reaction observed for AZABN relative to DMABN and DEABN. [5a, 10] With the XABN4Fs in MeCN, the shortest decay time t 2 has a similar value (around 0.09 ps) for all five molecules.…”
contrasting
confidence: 74%
“…It is possible that the slower picosecond rise time of the ICT states in ethanol, as compared to acetonitrile, is related to H-bonding in ethanol. 23 To summarize, our data suggest the existence of two charge-transfer states of DMABN in polar solvents, namely, the dark TICT state formed form the ‫ء‬ state and the fluorescent ICT state formed from the LE state. Differing time scales of the two ICT states indicate the lack of communication ͑i.e., rapid population equilibration͒ between them.…”
mentioning
confidence: 58%